Diagnosis Kesulitan Belajar dalam Perspektif Al-Qur’an - Tanuri Abu Fatih; Husnul Khotimah; Mujiono Mujiono (Journal on Education, 2024)
This research aims to determine the learning difficulties experienced by a student from the perspective of the Koran. Learning difficulties can be influenced by various factors, ranging from learning styles, learning concentration problems, having unique learning preferences, different learning methods, health problems, lack of student motivation to learn, environmental problems, and emotional problems and interest in learning. Verses originating from the Koran are used as a basis for the analysis. If the learning methods used do not suit a person's learning style, they may have difficulty understanding and retaining information. Therefore, individuals must know their own learning styles to adopt appropriate learning strategies. As a basis for the analysis, verses originating from the Koran are used. This research is library-based with qualitative methods and data sources from journal articles, books, or observations of phenomena occurring in the world of education today.